Influence of martensitic configuration on hysteretic properties of Heusler films studied by advanced imaging in magnetic field and temperature. (December 2021) - Takhsha Ghahfarokhi, Milad; Chirkova, Alisa; Maccari, Fernando; Casoli, Francesca; Ener, Semih; Skokov, Konstantin P.; Cabassi, Riccardo; Gutfleisch, Oliver; Albertini, Franca
Abstract: Ferromagnetic-shape-memory (FSM) Heusler compounds are an important class of multifunctional materials having promising applications in a vast variety of areas such as actuating, sensing, energy harvesting, spintronics and multicaloric cooling. Their multifunctionality stems from a reversible martensitic phase transition. However, their full exploitation is prevented by some undesirable characteristics of the martensitic transition: thermal hysteresis and broad transition. We studied here the role of specific martensitic configurations on the transition characteristics. By advanced magnetic force microscopy imaging in a wide temperature (260–350 K) and magnetic field range (up to 14 T) we directly observed the nucleation and the self-accommodation of the martensitic twinning configurations under zero-field, isofield and isothermal conditions. The experiments were performed on Ni-Mn-Ga epitaxial thin films with martensitic twinning configurations made of both X- and Y-type, which are characterized by different orientations of the twinning planes (i.e. at 45° and 90° degrees to the (001) MgO substrate, respectively). We have found that between the two possible twinning configurations, the Y-type, which nucleates first, shows a significantly smaller thermal hysteresis as well as a sharper phase transition with respect to X-type twinning configuration, for all the three investigated conditions. Graphical abstract: Image, graphical abstract